2020
DOI: 10.33487/edumaspul.v4i2.837
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Motivation in Writing through Mind Mapping at Tomakaka University of Mamuju

Abstract: The aim of this research is to find out whether the use of mind mapping can motivate the students in writing. The method was used is mix method (Quantitative and Qualitative). The subject of this research was the second semester students of Tomakaka University of Mamuju. The data was collected and analyzed through scoring scale which includes the content, organization, vocabulary, language use and mechanics by using Jacob’s scoring rubric. Then, to find out the students are motivated through the method applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Similarly, the findings of this study support those of [ 77 ], which showed that using mind-mapping technique in the teaching of writing descriptive texts was effective in improving the motivation of EFL learners. Additionally, this study’s results are consistent with [ 78 ], whose research documented that the implementation of the mind-mapping technique led to a significant improvement in L2 students' writing performance and motivation.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the findings of this study support those of [ 77 ], which showed that using mind-mapping technique in the teaching of writing descriptive texts was effective in improving the motivation of EFL learners. Additionally, this study’s results are consistent with [ 78 ], whose research documented that the implementation of the mind-mapping technique led to a significant improvement in L2 students' writing performance and motivation.…”
Section: Discussionsupporting
confidence: 90%
“…15, No. 11;2022 in writing, but students become self-regulation of what they are going to write and making them more motivated to finish their writing (Hasanah & Ali, 2020). A mind map may also be utilized as a writing instrument to help learners generate ideas, and in L2 writing, learners with strong motivation write in the target language because it interests them (Sabarun, El-Muslimah, & Muhanif, 2021).…”
Section: The Links Between a Mind Map And L2 Writingmentioning
confidence: 99%
“…The effort of stimulating students' ideas can be applied by using some media of learning or another method can motivate students to learn writing (Hasanah and Ali, 2020). The use of media in teaching and learning can be important to create an interesting and enjoyable atmosphere, especially in teaching writing (Maiza and Nurcahyoko, 2020).…”
Section: Introductionmentioning
confidence: 99%